Expenditure on Scientific Research and Its effect on Economic Growth in Arab States (Journal of Hama University, 2021)
This research comes for in trying to state the expenditure on R&D as an input of research and development in Arab countries focusing in case of Syria and determine to what extent the ERD contribute in enhancing the economic growth during 2005 to 2018 period according to data availability. The research uses the analytical descriptive method by reviewing literatures and available data about R&D provided by international organizations such as ESCWA, UNESCO, UN and World Bank and analyze these data by using SPSS program v.25. 2017. The research conclude mainly that, the positive correlation between GERD and GDP and economic growth as a result, and the statistical analysis indicate that the correlation between GERD and GDP is week and at lower level in most Arab countries as compared with international standards, where the percentage of GERD to GDP does not exceed 1%, this due to low contribution of private sectors in financing of R&D where the contribution of public sector is noticeable clearly in most Arab states, in addition to the higher percentage of R&D funding in most Arab countries depends on governmental funds which are unprofitable in its nature and this affects the return on investment of R&D outputs.